Analisis Penerapan Prinsip Tata kelola pada Lembaga Wakaf di Provinsi Riau - Zulhelmy; Abrar (UIR Press, 2018)
This study aims to see how the application of governance principles is applied to waqf institutions in Riau Province. The research method used is descriptive analytical, namely comparing the description of the implementation of the principles of governance practices in the waqf institution, and analyzing them using existing theories. The study population was waqf institutions in Riau province, while the study sample was LNW Ibadurrahman Duri Bengkalis on the grounds of the most active waqf institutions. The research respondents were 21 people. The results of his research are that in general the five principles of governance, namely transparency, accountability, responsibility, independence, equality and fairness have been applied well. It's just that what is not maximal is the principle of equality and fairness.